2019
DOI: 10.1021/acs.accounts.9b00097
|View full text |Cite
|
Sign up to set email alerts
|

The Prospect of Photochemical Reactions in Confined Gel Media

Abstract: Conspectus Nature is intrinsically able to control kinetics, conversion, and selectivity of biochemical processes by means of confined reaction environments such as enzyme pockets, bilayer membranes, micelles, vesicles, cells, or bioorganic frameworks. The main reason for this fact is the optimal molecular alignment and restricted motion of reactant molecules compared to those found in bulk solution. Under this inspiration, a number of synthetic photo-nanoreactors based on supramolecular self-assembled systems… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 48 publications
0
50
0
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9] Driven by the oen unexpected and appealing effects of nano-connement on chemical and physical properties, development of nano-reactors towards rational control of chemical reactivity by design has turned into one of the most thriving areas of contemporary research in chemistry. [10][11][12][13][14][15][16][17][18][19][20][21] For such a control to be truly rational, accurate understanding of the atomistic details of a given reaction in terms of stoichiometry, structure and interactions is required, together with quantication of the mutual effects that the nano-conned species and the nano-conning reactor exert on one another. However, to our knowledge, this has not been achieved to date with simultaneous resolution of the systems' stoichiometry, structure and dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] Driven by the oen unexpected and appealing effects of nano-connement on chemical and physical properties, development of nano-reactors towards rational control of chemical reactivity by design has turned into one of the most thriving areas of contemporary research in chemistry. [10][11][12][13][14][15][16][17][18][19][20][21] For such a control to be truly rational, accurate understanding of the atomistic details of a given reaction in terms of stoichiometry, structure and interactions is required, together with quantication of the mutual effects that the nano-conned species and the nano-conning reactor exert on one another. However, to our knowledge, this has not been achieved to date with simultaneous resolution of the systems' stoichiometry, structure and dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…[ 27,28 ] Previous studies have shown that TTA‐UC hydrogels can be synthesized, but none have reported hydrogels containing cells dispersed within a 3D scaffold. [ 15,29 ] In a recent eloquent study, Pluronic‐based gels were simply used as a light source (NIR‐to‐blue light) placed above 2D cultures of hippocampal neurons to trigger optogenetic responses. However, we note that similar optogenetic responses can be observed in 2D cultures by direct irradiation with blue light.…”
Section: Resultsmentioning
confidence: 99%
“…Dynamics in nanoconfined liquids is a large and diverse topic, ranging across fundamental physics to materials and biology. [68][69][70][71] Here we focus on those particular measurements of bulk liquid dynamics which inform the modelling of excited state reactions in confined media (with a particular focus on aqueous nanodroplets confined in inverse micelles) and specifically those measurements which either directly or indirectly yield the ultrafast C(t) required to model excited state reactions, as described in Section 3. These methods include the ultrafast optical Kerr effect (OKE), [72][73][74][75] ultrafast transient infrared (TRIR) and 2D IR spectroscopies 76,77 and solvation dynamics through time resolved fluorescence measurements of S(t).…”
Section: Dynamics In Confined Liquidsmentioning
confidence: 99%